Integrating the Early Warning Scoring System (EWSS) into Nursing Students’ Assessment to Enhance Critical Thinking and Optimize Patient Care in Inpatient Settings - Erik Irham Lutfi; Idola Perdana Sulistyoning Suharto; Sri Haryuni; Meirna Eka Fitriasnani; Achmad Wahdi (Universitas STRADA Indonesia, 2026)
Background: High-quality nursing care begins with an accurate and comprehensive patient assessment. The Early Warning Scoring System (EWSS) is a vital tool in inpatient units for monitoring vital signs and detecting early signs of clinical deterioration, enabling timely intervention. However, field observations indicate that nursing students often lack a practical understanding and the ability to apply EWSS, leading to passivity and uncertainty in clinical decision-making. Therefore, the development of EWSS-based initial assessments within nursing care reports is essential to enhance students' critical thinking and rational intelligence in clinical practice.Purpose: This study aims to develop and implement an EWSS-based initial assessment model that enables students to integrate assessment findings, scoring values, and appropriate clinical interventions. Through the interpretation of EWSS scores, students are expected to improve their clinical reasoning and decision-making skills within inpatient nursing services.Methods: This study employed a comparative analytical quantitative design. The research was conducted in the inpatient wards of a hospital in East Java. The population consisted of all nursing profession students (Ners) undergoing clinical practice in 2024, with a total sample size of 28 respondents. The independent variable was the nursing care report integrated with EWSS indicators, while the dependent variable was the students' rational intelligence in clinical decision-making related to EWSS outcomes. Data were collected using initial assessment observation sheets supplemented with EWSS. Statistical analysis was performed using the Wilcoxon test to determine differences before and after the intervention.Results: The integration of EWSS parameters into nursing students' assessment instruments significantly improved their ability to accurately interpret patients' clinical conditions and guided them in determining interventions, thereby enhancing rational intelligence. Conclusion: Early exposure to EWSS among students ultimately supports the creation of safer (patient safety) and more effective nursing care across all clinical practice settings.